Star Wars. Inquisitors - Barnes, Rodney (Producer) (Marvel Worldwide, Inc., 2024)
"Weapons of the Emperor sent out into the galaxy to track down and kill any Jedi who survived Order 66, the ruthless Inquisitors are among the most skilled and deadly threats to those who served the light side of the Force. But buried in the annals of Jedi lore is the story of Tensu Run, the Jedi knight who faced the Inquisitors and Darth Vader! What became of him, and why did the Empire so greatly fear his existence? Prepare to find out why Tensu Run is on Darth Vader's most-wanted list--and what threat he poses to the Dark Lord!"--